The great destroyers - Richmond, Caroline Tung (2021)
Jo Linden lives in a world where there are no atomic weapons, and the Cold War between the United States and the Soviet Union is played out in the Pax Games, fought with powerful robotic mecha war machines operated by young pilots; Jo needs the prize money to save her father's mecha repair shop, and keep what is left of her family together, but when competing pilots start dying from poisoning, Jo finds herself caught up in Cold War politics and political conspiracy and she discovers that it is not only her family's survival at stake--she may have to prevent World War III.
Ages 12 and up.
Grades 7-9.
Keywords: Mecha (Vehicles) -- Juvenile fiction; Robots -- Juvenile fiction; World politics -- Juvenile fiction; Conspiracies -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Alternative histories (Fiction); Adventure stories; Mecha (Vehicles) -- Fiction; Robots -- Fiction; Conspiracies -- Fiction; Fathers and daughters -- Fiction; Brothers and sisters -- Fiction; Adventure and adventurers -- Fiction; Alternative histories (Fiction); Action and adventure fiction